Temperature, climate change, and household financial behaviour: Evidence from Viet Nam - Sefa Awaworyi Churchill; Trong-Anh Trinh; Michael Danquah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We examine the impact of temperature shocks and climate change on household financial behaviour in Viet Nam. To do so, we first estimate the effect of temperature on household borrowing and savings using Vietnamese longitudinal data that matches satellite reanalysis temperature data with household information over the period 2008 to 2016. We find that an additional day with an average temperature of greater than 30êC, relative to the number of days in the 18-22êC range, is associated with a 6.3 per cent decrease in household savings and a 1.4 per cent increase in household borrowing. In the case of household savings, we find that the effects of temperature shocks are more pronounced on informal savings than formal savings. Further, total agricultural production and rice production are mechanisms through which temperature shocks influence household savings and borrowing. Specifically, by reducing the level of agricultural production, (hot) temperature shocks decrease household savings and increase household borrowing. Our estimates suggest that over the next century, under the conventional trajectory in which countervailing measures are not adopted to address climate change, climate change will be responsible for an additional 0.124 standard deviation decrease in household savings and a 0.102 standard deviation increase in household debt.
Keywords: Q51; Q54; G02; D14; 330; temperature; weather; climate change; savings; borrowing; Viet Nam